The Acalypha siamensis leaf as natural dye in eco-print - Hapsari, Natalia Diyah; Listyarini, Risnita Vicky; Handoyo, Luisa Diana; Feroniasanti, Yoanni Maria Lauda; Hapsari, Intan Putri; Tan, Andreas Felix; Darmanto, Elsie Gracia Putri; Abuk, Agnes Selfiana Irma; Fitriani, Helena; Krista, Brigitta Della Ocha (Pascasarjana Universitas Negeri Medan, 2024)
The use of synthetic dyes in the textile industry has a negative impact on the environment. Therefore, it is necessary to explore natural dyes that are more environmentally friendly. The aim of this research is to find natural dyes from Acalypha siamensis leaves. In this research, compounds contained in A. siamensis extract were identified using FT-IR and GC-MS instruments, then simulations were carried out of the reactions that occurred between cinnamaldehyde (E), cellulose in cotton, and alum mordant using quantum chemistry software. ORCA 5.0.2 and Visual Molecular Dynamics (VMD). The cinnamaldehyde compound is the main constituent compound in A. siamensis leaf extract. Based on the simulation results: the reaction between cinnamaldehyde (E), cellulose in cotton fabric, and alum mordant is energetically favorable. The reaction simulation results are in line with experimental research, the reaction of cellulose in cotton fabric, alum mordant, and cinnamaldehyde produces a brownish green color. A. siamensis leaves have potential as a dye in eco-prints.